Cost-effectiveness of psychological and psychosocial interventions for adults, children and young people who have self-harmed - Keith Hawton; Navneet Kapur; Karen Lascelles; Faraz Mughal; Ferruccio Pelone; Stephen Pilling; Ifigeneia Mavranezouli; Rachel Connolly; Katrina G Witt; Amanda Wildgoose; Angela Childs (BMJ Mental Health, 2024)
Background Self-harm is a major health issue resulting in high societal costs. Few psychological and psychosocial interventions have shown effectiveness in reducing repeat self-harm.Objective To assess the cost-effectiveness of psychological and psychosocial interventions that have shown evidence of effectiveness in adults and CYP (children and young people) who have self-harmed.Methods Using effectiveness data from Cochrane reviews, we developed two decision-analytical models to compare costs and quality-adjusted life years (QALYs) of cognitive behavioural therapy (CBT)-informed psychological therapy added to treatment as usual (TAU) versus TAU alone for adults who have self-harmed, and of dialectical behavioural therapy for adolescents (DBT-A) versus enhanced TAU for CYP who have self-harmed, respectively, from a National Health Service and personal social services perspective in England. Other model input parameters were obtained from published sources, supplemented by expert opinion.Findings The incremental cost-effectiveness ratio (ICER) of CBT-informed psychological therapy added to TAU versus TAU alone for adults who have self-harmed was £9088/QALY. The ICER of DBT-A versus enhanced TAU for CYP who have self-harmed was £268 601/QALY. Results were overall robust to the alternative scenarios tested.Conclusions and clinical implications CBT-informed psychological therapy appears to be cost-effective for adults who have self-harmed, which contributes to evidence for its implementation in services. Currently, DBT-A does not seem to be cost-effective for CYP who have self-harmed. The economic analyses were informed by clinical evidence of moderate-to-low (CBT) and low (DBT-A) quality. Further clinical and economic evidence for DBT-A and other psychological and psychosocial interventions for people who have self-harmed is required.